The Automated Breast Volume Scanner (ABVS): initial experiences in lesion detection compared with conventional handheld B-mode ultrasound: a pilot study of 50 cases - Wojcinski S; Farrokh A; Hille U; Wiskirchen J; Gyapong S; Soliman AA; Degenhardt F; Hillemanns P (Dove Medical Press, 2011)
Sebastian Wojcinski1, Andre Farrokh1, Ursula Hille2, Jakub Wiskirchen3, Samuel Gyapong1, Amr A Soliman1,4, Friedrich Degenhardt1, Peter Hillemanns21Department of OB/GYN, Franziskus Hospital, Bielefeld, Germany; 2Department of OB/GYN, Hannover Medical School, Hannover, Germany; 3Department of Radiology, Franziskus Hospital, Bielefeld, Germany; 4Department of OB/GYN, Faculty of Medicine, University of Alexandria, Alexandria, EgyptAbstract: The idea of an automated whole breast ultrasound was developed three decades ago. We present our initial experiences with the latest technical advance in this technique, the automated breast volume scanner (ABVS) ACUSON S2000TM. Volume data sets were collected from 50 patients and a database containing 23 women with no detectable lesions in conventional ultrasound (BI-RADS®-US 1), 13 women with clearly benign lesions (BI-RADS®-US 2), and 14 women with known breast cancer (BI-RADS®-US 5) was created. An independent examiner evaluated the ABVS data on a separate workstation without any prior knowledge of the patients’ histories. The diagnostic accuracy for the experimental ABVS was 66.0% (95% confidence interval [CI]: 52.9–79.1). The independent examiner detected all breast cancers in the volume data resulting in a calculated sensitivity of 100% in the described setting (95% CI: 73.2%–100%). After the ABVS examination, there were a high number of requests for second-look ultrasounds in 47% (95% CI: 30.9–63.5) of the healthy women (with either a clearly benign lesion or no breast lesions at all in conventional handheld ultrasound). Therefore, the specificity remained at 52.8% (95% CI: 35.7–69.2). When comparing the concordance of the ABVS with the gold standard (conventional handheld ultrasound), Cohen’s Kappa value as an estimation of the inter-rater reliability was κ = 0.37, indicating fair agreement. In conclusion, the ABVS must still be regarded as an experimental technique for breast ultrasound, which definitely needs to undergo further evaluation studies.Keywords: breast cancer, automated breast ultrasound, automated breast volume scanner, ABVS